Revealing the peculiarities of average bicoherence of frequencies in the spectra of dangerous parameters of the gas environment during fire - Pospelov, Boris; Andronov, Vladimir; Rybka Evgenіy; Chubko, Larysa; Bezuhla, Yuliia; Gordiichuk, Svitlana; Lutsenko, Tatiana; Suriadna, Nataliia; Hryshko, Svitlana; Kushchova, Tetyana (Eastern-European Journal of Enterprise Technologies, 2023)
The object of this study is a change in the hazardous parameters of the gas environment when materials are ignited in the premises. The subject is the features of the average bicoherence of the frequencies of the spectra of changes in the hazardous parameters of the gas environment when materials are ignited. The importance of such studies is based on the fact that the examined features can be used for the early detection of fires. The value of the average bicoherence is proposed to be determined for each frequency, taking into account the average value of the cosine argument of the complex bispectrum for a given frequency interval. It was established that the values of the average bicoherence of the spectrum of changes in the temperature of the gaseous medium in the interval of no ignition of the materials, averaged by frequency in the range of 0–2 Hz, lie in the range from ‒0.052 to ‒0.35. At the same time, the frequency-averaged values of mean bicoherence at the ignition interval of materials lie in the range of ‒0.128 to +0.155. Averaged in the frequency range of 0–2 Hz, the value of the mean bicoherence of the spectrum of changes in smoke density in the interval of absence of ignition of materials lies in the range from ‒0.018 to +0.568. In the presence of fires, this value is in the range from –0.244 to +0.23. At the same time, the average value of the average bicoherence of the spectrum of changes in the concentration of carbon monoxide of the gas medium for test materials, averaged in the range from 0 to 2 Hz, ranges from +0.016 to +0.109. In the case of ignition of materials, the average values range from +0.0007 to +0.053, except for ignition of wood (+0.117). In general, the revealed features of the average bicoherence of the frequency components of the spectra of changes in the hazardous parameters of the gas environment indicate the possibility of their use to identify fires and prevent fires